Enhancing students’ participation through differentiated strategies in the ESL classroom / Anisah Khairina Ismail ... [et al.] - Ismail, Anisah Khairina; Gopal, Revathi; Swaran Singh, Charanjit Kaur; Maniam, Mahendran; Nallaluthan, Kesavan (Universiti Teknologi MARA Cawangan Kedah, 2022)
This study aims to investigate the application of differentiated strategies in the ESL form 4 to improve students’ participation. Qualitative research design is employed. Samples consist of 25 students of mixed proficiency level. Purposive sampling was used in the selection of the samples. The instruments involved in data collection were an audio-video teaching session and the researcher’s reflective entry. The findings revealed that the types of differentiated strategies such as differentiation by instructions, the task given to students, the type and amount of support given by the teacher to the students, the outcome expected from students employed, time given to complete a task, supporting individual preferences and feedbacks given during the teaching and learning helped the students to participate actively in the ESL classroom